1997
DOI: 10.1262/jrd.43.235
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Cell Proliferation and Morphology of Ampullar Epithelium of the Mouse Oviduct during the Estrous Cycle.

Abstract: Abstract. We examined cell proliferation and morphological changes in the ampullar epithelium of mouse oviducts. Oviducts were labeled in vivo by administration of 5-bromo-2'-deoxyuridine (BrdU) on each day of the estrous cycle. The frequency of the ampullar S-phase epithelial cells labeled with BrdU changed according to the estrous cycle, with the highest proportion at proestrus. The morphology of the ampullar epithelia also changed during the estrous cycle. In estrus and metestrus, most of the ampullar epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Accordingly, we noted changes in the relative number of ciliated cells depending on estrous cycle stage and early pregnancy in C57BL/6 mice, albeit they were not as pronounced as those reported for the ICR mouse strain by Morita et al [38]. Those authors observed 76% and 90% frequency of nonciliated cells in the ampulla in estrus and metestrus, respectively, whereas we rather continuously counted approximately 30% for ampullar nonciliated cells.…”
Section: Noreikat Et Alsupporting
confidence: 47%
See 1 more Smart Citation
“…Accordingly, we noted changes in the relative number of ciliated cells depending on estrous cycle stage and early pregnancy in C57BL/6 mice, albeit they were not as pronounced as those reported for the ICR mouse strain by Morita et al [38]. Those authors observed 76% and 90% frequency of nonciliated cells in the ampulla in estrus and metestrus, respectively, whereas we rather continuously counted approximately 30% for ampullar nonciliated cells.…”
Section: Noreikat Et Alsupporting
confidence: 47%
“…Those authors observed 76% and 90% frequency of nonciliated cells in the ampulla in estrus and metestrus, respectively, whereas we rather continuously counted approximately 30% for ampullar nonciliated cells. This striking contrast may be due to strain differences, but it is also conceivable that the ampullar segments investigated by Morita et al [38] were taken closer to the isthmus than our samples. The major estrous cycle stagedependent change we observed was a 4-fold increase in the relative frequency of ciliated cells in the isthmus from proestrus (6%) to estrus (24%) with subsequent return to 10%, indicating particularly well-sustained transport capacity at ovum pickup.…”
Section: Noreikat Et Almentioning
confidence: 64%
“…The antagonizing effect of progesterone was observed on feline oviducts when estrogen and progesterone were administered sequentially (West et al, 1976). Therefore, secretory cells like OA-ab cells increase activity under the influence of ovarian estrogen during proestrus and estrus (Buhi et ah, 1989;Morita et al, 1997aMorita et al, , 1997b. As the concentration of progesterone increases, estrogen's effect is antagonized during metestrus and diestrus.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the GAGs in the fluid secreted by the genital organs of bitches may serve to accelerate the capacitation of dog sperm. The secretory function of oviductal epithelial cells has been found to become active in the estrous period of different species [1,18,27], and non-ciliated cells in the ampulla of the oviduct have been observed to secrete large amounts of glycoproteins in estrous ewes [27] and mice [26]. Furthermore, it has been reported that the oviductal fluid of estrous cows contains a large volume of GAGs [2,8,17], and GAGs have been detected not only in the oviductal fluid of the cow [17] and ewe [18] but in their uterine fluid as well.…”
Section: Discussionmentioning
confidence: 99%